Protective effect of hydroalcoholic extract of Teucrium polium on diabetes-induced testicular damage and serum testosterone concentration - Ramin Salimnejad; Ghasem Sazegar; Mohammad Javad Saeedi Borujeni; Seyed Mojtaba Mousavi; Fatemeh Salehi; Fatemeh Ghorbani (Shahid Sadoughi University of Medical Sciences, 2017)
Background: Diabetes has an adverse effect on spermatogenesis by rising oxidative stress. Objective: The aim of this study was to investigate the effect of Teucrium Polium extract administration on spermatogenesis and testicular structure in diabetic rats induced with Streptozotocin. Materials and Methods: 32 male Wistar rats were randomly divided into four groups (n=8/each): control group, diabetic group received distilled water, and two experimental groups included diabetic rats treated with 50 and 100 mg/body weigh of Teucrium Polium extract for 6 six weeks. After six weeks, the left testis had been removed and the morphometrical study was performed. Blood samples were collected from the ophthalmic veins of the rats and plasma levels of glucose and testosterone hormone were measured afterward. Results: The reduction in diameters of the seminiferous tubules and thickening of the wall of the seminiferous tubules (p=0.05) were seen in diabetic rats. Also, the degenerative changes in cells arrangement have been observed. Statistical analysis showed the use of Teucrium Polium significantly improved the above disorders in treatment group (100 mg/BW) in contrast to the non treated diabetic group (p=0.05), but no significant difference was seen between the experimental group treated with 50 mg/BW of Teucrium polium and diabetic group (p=0.08). These data also revealed that treatment of diabetic rats with 100 mg/BW of Teucrium Polium extract significantly improves the change in serum glucose (p=0.001) and testosterone (p=0.03). Conclusion: The results of the present study indicate that diabetes produces degenerative changes in the testis of rats and administration of Teucrium polium reduces complications resulted from diabetes